Alteration of iron metabolism of elite female distance runners in intensity training - Bayar T.; Bao, D. (Modern Applied Science, 2008)
The hemoglobin (Hb), serum Iron (SI), serum ferritin, serum transferrin (Tr), serum transferrin receptor (sTfR) concentration, Erythrocyte hemoglobin distribution width(RDW) and erythropoietin(EPO) in adults are suggested to provide a sensitive measure of iron depletion and the serum ferritin (Ferr) concentration is able to indicate the entire range of iron status, from iron deficiency to iron overload. However, little is known about those indexes in elite female distant runners. The objective of this study was to determine the above indexes in intensity training of 8 elite female distant runners two months ahead of national competition. Result showed that Hb concentration decreased in second sampling point and then recovered; SI concentration firstly decreased then increased, but it was not significant; Tr concentration, RDW and EPO level increased in second sampling point then fell to baseline; there was no significant difference in Ferr and sTfR concentration. It can be concluded that due to intensity training, iron metabolism in the initial stage of training was disturbed and then modulated in following training phase.